Error Detecting Dual Basis Bit Parallel Systolic Multiplication Architecture over GF(2m) - Singh, Ashutosh Kumar; Bera, A.; Rahaman, H.; Mathew, J.; Pradhan, D.k. (IEEE Proceeding, 2009)
This paper presents an error tolerant hardware efficient VLSI architecture for bit parallel systolic multiplication over dual base, which can be pipelined. This error tolerant architecture is well suited to VLSI implementation because of its regularity, modular structure, and unidirectional data flow. The length of the largest delay path and area of this architecture are less compared to the bit parallel systolic multiplication architectures reported earlier. The architecture is implemented using Austria Micro System's 0.35um CMOS technology. This architecture can also operate over both the dual-base and polynomial base.